Pressure drop and flow distribution in parallel-channel configurations of fuel cells: Z-type arrangement - Wang, Junye (International journal of hydrogen energy, 2010)
A general theoretical model based on mass and momentum conservation has been developed to solve the flow distribution and the pressure drop in Z-type configurations of fuel cells. While existing models neglected either friction term or inertial term, the present model takes both of them into account. The governing equation of the Z-type arrangement was formulated to an inhomogeneous version of the U-type one. Thus, main existing models have been unified to one theoretical framework. The analytical solutions are fully explicit that they are easily used to predict pressure drop and flow distribution for Z-type layers or stacks and provide easy-to-use design guidance under a wide variety of combination of flow conditions and geometrical parameters to investigate the interactions among structures, operating conditions and manufacturing tolerance and to minimize the impact on stack operability. The results can also be used for the design guidance of flow distribution and pressure drop in other manifold systems, such as plate heat exchanges, plate solar collectors, distributors of fluidised bed and boiler headers.